Effect of clinical rotation on attitude of medical students towards psychiatry and mental patients: a cross-sectional study from Western Rajasthan - Agrawal, Aditi; Gehlot, Sanjay; Singhal, Ashok; ., Amandeep (International Journal of Research in Medical Sciences, 2021)
Background: People with mental illnesses experience extreme stigmatization and discrimination despite their ubiquitous presentation. Studies have reported that these negative stereotypes are shared by health care professionals too. Attitude of undergraduate medical students towards psychiatry is vital as it reflects their willingness to deal with psychiatric and behavioral disorders in general practice. Methods: A descriptive cross-sectional study was conducted in a government medical college in Rajasthan to explore the impact of sociodemographic variables and undergraduate psychiatry training on the attitude of medical students towards mental illness and psychiatry. 105 first year MBBS students and 75 interns participated in the study. Attitude towards mental illness (AMI) scale and attitude towards psychiatry-30 (ATP-30) scale were used to document AMI and ATP respectively. Data collected were analyzed using SPSS statistical software and appropriate tests were used to compare mean scores of both groups. Results: There was no statistically significant difference on AMI and ATP scores between the undergraduate medical students and interns. Females, students belonging to urban setting and more educated families had a favorable attitude towards psychiatric patients. A notable shift in scores on ATP scale towards positive side was reflected between male MBBS students and interns and among students coming from rural background with exposure to medical curriculum. Conclusions: No attitude change was observed in majority of participants indicating need for greater emphasis on mental health and psychiatry.